Amorphous high-entropy phosphide nanosheets with multi-atom catalytic sites for efficient oxygen evolution - Li, Xiumin (2025)
The alkaline oxygen evolution reaction (OER) mainly encompasses four elementary reactions, involving intermediates such as HO*, O*, and HOO*. Balancing the Gibbs free energies of these intermediates at a single active site is a challenging task. In this work, a high-entropy metal-organic framework incorporating Fe, Ni, Co, Cu, and Y metal elements is synthesized using an electrodeposition method, which then serves as a template for preparing a high-entropy phosphide/carbon (FeCoNiCuYP/C) composite. Notably, the obtained composite exhibits an amorphous structure with multiple catalytically active sites. Combined theoretical calculations and experimental measurements reveal the critical roles of Co/Ni and Fe atoms in tuning the electronic structure of FeCoNiCuYP and optimizing the binding strength of intermediates. Furthermore, Fe and Ni/Co sites prefer to stabilize the HO* and HOO* intermediates respectively, conducive to breaking their scaling relation of Gibbs free energy during OER. Owing to its fine-tuned composition and the synergistic effect of multiple active sites, the FeCoNiCuYP/C electrocatalyst demonstrates superior OER performance in alkaline solutions, requiring a mere 316 mV overpotential to yield 100 mA cm-2 current density with excellent stability. This work provides an innovative route to design efficient high-entropy electrocatalysts, holding significant promise for cutting-edge electrocatalytic applications.